Analysis of the importance of communicative and technical English language, in the Professional Schools of Mining Engineering of Peru for the innovation of extractive technologies of future professionals, 2019 - Quispe Perez, Marcos Luis; Parra Ocampo, Paola; Hinostroza, Erika; Colque , Daniel (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This project has as general objective to determine the relationship that exists between university students of the School of Mining Engineering and the proficiency of the communicative and technical English language, becoming familiar with innovations in extractive technologies during their academic preparation for their professional development in the labor field nationally and internationally 2019.